Engineering community spirit: the pre-figurative politics of affective citizenship in Dutch local governance. Issue 8 (16th November 2016) - de Wilde, Mandy; Duyvendak, Jan Willem
Abstract: Over the past two decades, communitarian criticisms of the lack of public engagement and a sense of local belonging have inspired extensive debates across Western Europe on how best to govern deprived urban neighbourhoods. One governmental strategy has been to engineer neighbourhood communities as localised, collective spheres of belonging. In this article, we show how 'governing through affect' has been part of Dutch neighbourhood policy since the turn of the millennium. Through an in-depth study of a community participation programme in a deprived Amsterdam neighbourhood, we analyse how policy practitioners use 'sensitising policy techniques' to enhance social cohesion and encourage communitarian citizenship among neighbourhood residents. Although governments often speak of 'communities' as self-evident entities, we argue that communities are better understood as enactments where discourses of neighbourliness, proximity, intimacy and familiarity encourage a localised, collective sense of belonging – a governmental strategy that mimics the 'pre-figurative' politics of radical social movements.